2017
DOI: 10.1186/s12886-017-0470-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid concentration is associated with hypertensive retinopathy in hypertensive chinese adults

Abstract: BackgroundThis cross sectional investigation included 12,966 subjects with hypertension, a cohort of the China Stroke Primary Prevention Trial (CSPPT), a randomized, multicenter clinical trial. This study aimed to explore the correlation between serum uric acid (SUA) concentration and hypertensive retinopathy in hypertensive adults.MethodsDiagnosis of hypertensive retinopathy was determined by non-mydriatic fundus photography and classified with Keith-Wagener-Barker (KWB) system. The correlation of SUA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
1
12
0
4
Order By: Relevance
“…Uric acid crystal and ROS are able to activate inflammasome. It is reported that serum uric acid concentration is associated with hypertensive retinopathy in hypertensive Chinese adults [7]. Thus, ROS and MDA increased and the possible association between increased IL-β 1 and inflammasome activation in the eyes with systemic repercussion can be envisaged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uric acid crystal and ROS are able to activate inflammasome. It is reported that serum uric acid concentration is associated with hypertensive retinopathy in hypertensive Chinese adults [7]. Thus, ROS and MDA increased and the possible association between increased IL-β 1 and inflammasome activation in the eyes with systemic repercussion can be envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…Chan & Zhu et al [5,6] in a review and meta-analysis study observed a significant association between gestational hypertensive disorders and development of retinopathy of prematurity. High serum level of uric acid correlated with the presence of hypertensive retinopathy [7], stroke, diastolic dysfunction and renal abnormality [8][9][10][11]. In spite of several studies on diabetic retinopathy, there are few reports in the literature comparing diabetic and hypertensive retinopathy.…”
Section: Introductionmentioning
confidence: 96%
“…Миллионы людей в мире страдают от заболеваний, вызванных гипертонией [1]. Распространенность гипертонической ретинопатии составляет 75,95 % среди людей с гипертонической болезнью [2].…”
Section: актуальность и распространенностьunclassified
“…Chen и соавт. выявлена ключевая роль в возникновении гипертонической ретинопатии мочевой кислоты в высоких концентрациях в сыворотке крови [2]. Увеличение концентрации мочевой кислоты в 1 мг/дл достоверно ассоциировалось с гипертонической ретинопатией.…”
Section: актуальность и распространенностьunclassified
See 1 more Smart Citation